Risk prediction models for malignant cerebral edema after endovascular therapy in patients with acute anterior circulation large vessel occlusion stroke: a systematic review and meta-analysis - Yuan, Yuan; Cai, Weixin; Feng, Yadi; Zhang, Ran; Wang, Cuixue; Luo, Yifan; Yi, Xiaoping (Frontiers in Neurology, 2026)
BackgroundEndovascular therapy (EVT) is proven to be both effective and safe for treating acute anterior circulation large vessel occlusion stroke (ACLVOS). Malignant cerebral edema (MCE) can emerge as a severe complication following ET. Predicting acute ACLVOS patients at risk of MCE is crucial for prevention, management, and medical decision-making. The predictive performance and predictive factors of MCE models are not yet well understood.AimsTo identify risk prediction models and potential predictive factors for malignant cerebral edema (MCE) after endovascular therapy (EVT) in patients with acute anterior circulation large vessel occlusion stroke (ACLVOS).Study designWe conducted a systematic search of studies using eight databases from inception until December 31st, 2024. Data extraction followed the critical appraisal and data extraction for systematic reviews of prediction modelling studies (CHARMS) Checklist. And We used the prediction model risk of bias assessment tool (PROBAST) tool to assess the risk of bias and applicability.ResultsWe included 21 articles identifying 30 MCE prediction models. The most common predictors of MCE were the National Institutes of Health Stroke Scale (NIHSS) score, collateral score, and Alberta Stroke Program Early Computed Tomography Score (ASPECTS). All included studies exhibited a high risk of bias. Seventeen studies raised significant applicability concerns, whereas five studies posed lower applicability concerns.ConclusionThis systematic review confirms the feasibility of predicting MCE risk after EVT in ACLVOS patients using existing models and highlights key predictive factors. However, the high risk of bias across studies limits their clinical applicability.Relevance to clinical practiceThis study empowers ICU nurses to accurately identify the risk levels of MCE and implement targeted monitoring strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024564544, CRD42024564544.